2019
DOI: 10.1016/j.still.2018.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Soil load support capacity increases with time without soil mobilization as a result of age-hardening phenomenon

Abstract: Soil compaction is a result of soil compression, and this effect depends on the pressure applied and the soil structure. Nevertheless, studies regarding the effects of long-term tillage systems on strengthening of particle bonds are scarce. Thus, we aimed to study the soil bond strengthening due to the age-hardening phenomenon using the soil load support capacity model of an Oxisol managed under different tillage systems in Southern Brazil. Soil samples were collected from three soil layers (0.0-0.10 m; 0.10-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
5
17
0
4
Order By: Relevance
“…The soil tilling in the planting row in the no-tillage system may have increased the PR in the wheel tracks (Cortez et al, 2014), while higher PR values were observed in the surface layers (0.00-0.10 m and 0.10-0.20 m) of the reduced-tillage system due to the action of the disks of the soil tillage implement. This result, as reported by Moraes et al (2018), is possible because the soil particles are rearranged, causing greater densification in the surface layers of the soil under reduced tillage.…”
Section: Resultssupporting
confidence: 57%
“…The soil tilling in the planting row in the no-tillage system may have increased the PR in the wheel tracks (Cortez et al, 2014), while higher PR values were observed in the surface layers (0.00-0.10 m and 0.10-0.20 m) of the reduced-tillage system due to the action of the disks of the soil tillage implement. This result, as reported by Moraes et al (2018), is possible because the soil particles are rearranged, causing greater densification in the surface layers of the soil under reduced tillage.…”
Section: Resultssupporting
confidence: 57%
“…The significant positive linear relationship between SWS and σ p has been reported in several studies [16,[50][51][52][53][54]. However, in the present study, σ p increased with an increase in SWS until 600 kPa under various SOM conditions and decreased when SWS exceeded 600 kPa (Figure 3).…”
Section: Relationship Between Soil Physiochemical and Mechanical Para...supporting
confidence: 69%
“…Adoption of no‐tillage in sugarcane fields can also provide many other benefits to soil, such as the reduction of erosion (Salem, Valero, Muñoz, Rodríguez, & Silva, 2015) and increase of soil carbon accumulation (Segnini et al, 2013; Tenelli et al, 2019). The latter is essential to improve soil physical quality in no‐tillage systems on a long‐term basis, because carbon acts by different mechanisms that improve soil aggregation (Tisdall & Oades, 1982) and contribute to soil restructuring through the age‐hardening phenomenon, which involves the rearrangement and binding of soil particles to form more stable soil aggregates that preserve a more complex and functional inter‐ and intra‐aggregate pore network (Cavalcanti et al, 2020; de Moraes et al, 2017, 2019). This study provided evidence that the creation of seedbeds is a good management practice to improve soil physical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate deleterious impacts of intensive machine traffic, conventional tillage with intense soil mobilization has been adopted once every 5–6 years during the (re)planting of sugarcane. However, conventional tillage induces loss of carbon (C)‐rich macroaggregates (Six, Elliott, & Paustian, 2000) and reduces soil bearing capacity (de Moraes, da Luz, Debiasi, Franchini, & da Silva, 2019), thus making it more susceptible to re‐compaction under subsequent machinery traffic. According to Barbosa et al (2019), the effectiveness of conventional tillage in promoting better soil physical conditions does not last beyond a second year, and then soil compaction under tilled soils achieves similar levels of those observed previously to tillage practices, mainly in the trafficked areas in inter‐row positions.…”
Section: Introductionmentioning
confidence: 99%